Posisi dan Stategi Pendidikan Islam di Eraglobalisasi - Mahmudi Mahmudi (FALASIFA : Jurnal Studi Keislaman, 2021)
ABSTRACT Opportunities and challenges of globalization require superior and competitive human resources, which need to be responded positively by Islamic education. These opportunities need to be fulfilled by utilizing all the positive potentials of globalization, spreading Islamic values ​​to the world as an effort to save humanity from the scularization virus that ignores the spiritual dimension in humans. In addition, Islamic education must develop a spiritual-based education that is fully supported by teachers, students and educational organizations that fully support prophetic transformational leadership, therefore the teaching and learning strategy can be developed in accordance with the demands of the times. Keywords: globalization, Islamic education, position, strategy ABSTRAK Peluang dan tantangan globalisasi membutuhkan sumber daya manusia yang unggul dan kompetitif, yang perlu direspon secara positif oleh pendidikan Islam. Peluang-peluang ini perlu dipenuhi dengan memanfaatkan semua potensi positif globalisasi, menyebarkan nilai-nilai Islam ke dunia sebagai upaya menyelamatkan manusia dari virus skularisasi yang mengabaikan dimensi spiritual dalam diri manusia. Selain itu, pendidikan Islam harus mengembangkan pendidikan berbasis spiritual yang didukung penuh oleh para guru, pelajar, dan organisasi pendidikan yang sepenuhnya mendukung kepemimpinan transformasional kenabian, oleh karena itu starategi pengajaran dan pembelajaran bisa dikemangakan sesuai dengan tuntutan zaman. Kata Kunci: globalisasi, pendidikan Islam, Posisi, Strategi